P03 Reporting of coronary artery calcification on non-gated pre-surgical CT thorax. (7th September 2020) - Rahiminejad, M; Patel, V; Bille, A; Benedetti, G; Preston, R; Mak, SM
Abstract : Introduction: Coronary artery calcification (CAC) is a known risk factor for myocardial infarction (MI). CAC score is demonstrated to have prognostic value in predicting the incidence of cardiovascular events. CAC can be visually estimated on non-gated CTs, even when not formally quantified. It is a strong prediction tool for risk stratification in the asymptomatic population. We noticed that CAC is not routinely reported as part of routine CT thorax. The aim of our study is to evaluate the percentage of CAC reported by radiologists, and if there is a link to peri-operative myocardial infarction (within 5 days of surgery). Methods: The study is retrospective and 100 ungated thoracic CTs acquired for lung cancer surgical planning are included. An ordinal score of 1 to 10 was visually assigned. The medical records of these patients were reviewed. Results: 61 out of 100 patients had CAC visible on their CTs. However, this was only mentioned in 1 report (1%). There was no peri-operative MI. 5 patients (5%) had MI in the past, and all of them had CAC. Conclusion: CAC is not routinely reported by our radiologists on non-gated thoracic CTs. Although there is no link to increased peri-operative myocardial infarction in our cohort, this is an opportunity for clinicians to risk stratify their patients. More awareness needs to be raised in our local institution to improve current practice.